2014
DOI: 10.1152/ajplung.00102.2014
|View full text |Cite
|
Sign up to set email alerts
|

CCN1 secretion and cleavage regulate the lung epithelial cell functions after cigarette smoke

Abstract: . CCN1 secretion and cleavage regulate the lung epithelial cell functions after cigarette smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
96
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 46 publications
5
96
0
Order By: Relevance
“…Chen et al (2016) demonstrated that EV from CSEexposed macrophages contain the pro-inflammatory alarmin high-mobility group box 1. Further, EV from CSE-exposed macrophages and epithelial cells, as well as EV isolated from BALF of smokers trigger release of interleukin-(IL-) 6, IL-8, and monocyte chemoattractant protein 1 (MCP1) by naïve pulmonary epithelial cells (Cordazzo et al 2014;Héliot et al 2017;Moon et al 2014). EV also promote upregulation of intercellular adhesion molecule 1 (Cordazzo et al 2014) and thus may contribute to inflammation and immune cell recruitment toward EV target cells.…”
Section: Promotion Of Pro-inflammatory Signalingmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al (2016) demonstrated that EV from CSEexposed macrophages contain the pro-inflammatory alarmin high-mobility group box 1. Further, EV from CSE-exposed macrophages and epithelial cells, as well as EV isolated from BALF of smokers trigger release of interleukin-(IL-) 6, IL-8, and monocyte chemoattractant protein 1 (MCP1) by naïve pulmonary epithelial cells (Cordazzo et al 2014;Héliot et al 2017;Moon et al 2014). EV also promote upregulation of intercellular adhesion molecule 1 (Cordazzo et al 2014) and thus may contribute to inflammation and immune cell recruitment toward EV target cells.…”
Section: Promotion Of Pro-inflammatory Signalingmentioning
confidence: 99%
“…The studies that report either induction (Cordazzo et al 2014;Héliot et al 2017;Moon et al 2014) or no induction ) of pro-inflammatory cytokines by CS(E)-induced EV in vitro have all employed similar exposure times, EV isolation techniques, and EV target cells (bronchial epithelial cells). Yet, the divergent results might be explained by the quantity of EV used in functional assays as Héliot et al (2017) obtained their positive results with 100-fold more EV than the quantity that resulted in negative results .…”
Section: Conflicting Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Since the authors suggest that the measured weight reduction and increased mortality are due to an increase of lung injury, it would be further necessary to analyze whether the lung morphology was phenotypically altered and whether the measured increase in bronchoalveolar lavage fluid neutrophil counts impacts the total content of immune cells infiltrating the lung. It is quite possible that the weight loss is simply due to CCN1-induced promotion of epithelial cell death and tissue loss that was previously found in mice with emphyseamatous changes after prolonged cigarette smoke exposure (8). All these issues would be worth to be analyzed in future studies to understand the pathophysiological role of CCN1 in injured lung tissue.…”
mentioning
confidence: 93%